The Relationship Between Financial Risk Premia and Macroeconomic Volatility: Issues and Perspectives on the Run-Up to the Turmoil - Massimiliano Marzo; Zhoushi Liu; Paolo Zagaglia (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2011)
This note sketches the issues that arise while interpreting the relation between macroeconomic volatility and financial risk premia from the perspective of the standard consumption-based asset pricing model. The relation arises from the fact that all assets are priced by the same 'pricing kernel', given by the inter-temporal marginal rate of substitution in consumption of the representative investor. Since the pricing kernel is a function of aggregate consumption, financial risk premia are positively related to consumption growth volatility. Therefore, from the perspective of this workhorse often employed in the academic debate, the persistent reduction in macroeconomic volatility can be considered a cause for the low average risk premia prevailing during the so-called Great Moderation, namely the period preceding the recent turmoil in financial markets. We challenge this view by shedding light on the issues that generate an inconsistent interpretation of the model outcomes. In particular, since the consumption-based model is geared towards asset prices consistent with macroeconomic fundamentals, we argue that it is not suited for interpreting current developments where underestimation of risk may have subsidized asset prices. In particular, according to the evidence for the Great Moderation, the model view suffers from observational equivalence.
Keywords: E43; G12; 330